2020
DOI: 10.2174/1573403x15666190522100041
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Analysis of Dyslipidemia Involvement in Coronary Artery Disease: A Narrative Review

Abstract: Background: Dyslipidemia is the main factor involved in the occurrence and progression of coronary artery disease. Objective: The research strategy is aimed at analyzing new data on the pathophysiology of dyslipidemia involvement in coronary artery disease, the modalities of atherogenic risk estimation and therapeutic advances. Method: Scientific articles published in PubMed from January 2017 to February 2018 were searched using the terms "dyslipidemia" and "ischemic heart disease". Results: PCSK9 contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…Cardiovascular diseases are the leading cause of morbidity and mortality worldwide [1]. These diseases are related to several risk factors especially dyslipidemia, which is a metabolic disorder that is manifested by elevated levels of plasma total cholesterol (TC), triglycerides (TG), and low-density lipoprotein cholesterol (LDL-C), along with a reduced level of high-density lipoprotein cholesterol (HDL-C) [2]. Dyslipidaemia is closely linked with occurrence and progression of several pathologies including atherosclerosis and its complications such as coronary artery disease [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular diseases are the leading cause of morbidity and mortality worldwide [1]. These diseases are related to several risk factors especially dyslipidemia, which is a metabolic disorder that is manifested by elevated levels of plasma total cholesterol (TC), triglycerides (TG), and low-density lipoprotein cholesterol (LDL-C), along with a reduced level of high-density lipoprotein cholesterol (HDL-C) [2]. Dyslipidaemia is closely linked with occurrence and progression of several pathologies including atherosclerosis and its complications such as coronary artery disease [2].…”
Section: Introductionmentioning
confidence: 99%
“…These diseases are related to several risk factors especially dyslipidemia, which is a metabolic disorder that is manifested by elevated levels of plasma total cholesterol (TC), triglycerides (TG), and low-density lipoprotein cholesterol (LDL-C), along with a reduced level of high-density lipoprotein cholesterol (HDL-C) [2]. Dyslipidaemia is closely linked with occurrence and progression of several pathologies including atherosclerosis and its complications such as coronary artery disease [2]. Several clinical trials confirmed that the reduction of plasma levels of TC, TG, and LDL-C induce a significant reduction of the morbidity and mortality rate related to these diseases [3].…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery disease (CAD) is the number one cause of mortality in industrialized countries (Dalen et al, 2014;Sidney et al, 2019). A risk factor associated with CAD is low high-density lipoprotein (HDL) cholesterol and apolipoprotein A-I (apo A-I) concentrations in plasma (Malakar et al, 2019;Mihăilă, 2020;Oikonomou et al, 2020;Stone & Grundy, 2019). Though increasing HDL/apo A-I levels may slow and reverse atherosclerosis (Lebherz et al, 2007;Shaw et al, 2008), approaches to increase apo A-I via various pharmaceutical agents have not been successful in preventing major adverse cardiovascular events (Feghaly & Mooradian, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…5 Single nucleotide polymorphism in a few genes is associated with high triglyceride (TG) and CHOL levels significantly contributing to dyslipidemia. 6 A gene associated with TG and CHOL level is the gene encoding for fatty acid-binding proteins (FABP2) located at the chromosome 4q2-q31, another gene apolipoprotein C3 gene (APOC3) located on the chromosome 11q23, allele *3238 C is also involved in the regulation of plasma TG levels. 7,8 The circulating lipid biomarkers, mainly polymorphism APOC3 (rs5128) and FABP2 (rs1799883), had been independently studied in diabetic patients, but the associations between these biomarkers and occurrence of dyslipidemia in nondiabetic patients had rarely been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Single nucleotide polymorphism in a few genes is associated with high triglyceride (TG) and CHOL levels significantly contributing to dyslipidemia. 6 A gene associated with TG and CHOL level is the gene encoding for fatty acid-binding proteins ( FABP2 ) located at the chromosome 4q2–q31, another gene apolipoprotein C3 gene ( APOC3 ) located on the chromosome 11q23, allele *3238 C is also involved in the regulation of plasma TG levels. 7 8 …”
Section: Introductionmentioning
confidence: 99%